The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1143/apex.4.021601
|View full text |Cite
|
Sign up to set email alerts
|

Strong Pressure Effect in the Sublimation from Tetracene Single Crystals and Development of Surface Cleaning Technique for Organic Semiconductors

Abstract: We studied the sublimation of tetracene single crystals under vacuum and 1 atm inert gas to develop the surface cleaning technique for organic semiconductors. It was found that the microscopic sublimation behavior is strongly dependent on the gas pressure.Nanometer-scale roughening is observed after heating in vacuum, while layer-by-layer sublimation was observed under 1 atm Ar gas. Reflection high energy electron diffraction of the topmost surface showed streak patterns, which shows surface contaminants were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…While Vollmer et al ascribed the cause of such defects to a cleavage process with adhesive tape, a disordered top surface layer on the tetracene single crystals was suggested by reflection high-energy electron diffraction experiments even without any mechanical cleavage procedure. 156 A probable molecular rearrangement for the top surface layer of the tetracene single crystal was also claimed through precise X-ray diffraction analyses. 157 ARUPS measurements of more surface insensitive conditions, e.g., under excitation by lower energy photons, may be a possible solution for accessing the valence band structures and hole effective mass of the bulk single crystal tetracene, which was successfully demonstrated for pentacene as discussed in the next subsection.…”
Section: Resultsmentioning
confidence: 88%
“…While Vollmer et al ascribed the cause of such defects to a cleavage process with adhesive tape, a disordered top surface layer on the tetracene single crystals was suggested by reflection high-energy electron diffraction experiments even without any mechanical cleavage procedure. 156 A probable molecular rearrangement for the top surface layer of the tetracene single crystal was also claimed through precise X-ray diffraction analyses. 157 ARUPS measurements of more surface insensitive conditions, e.g., under excitation by lower energy photons, may be a possible solution for accessing the valence band structures and hole effective mass of the bulk single crystal tetracene, which was successfully demonstrated for pentacene as discussed in the next subsection.…”
Section: Resultsmentioning
confidence: 88%
“…the in-plane mean crystallite size of C 60 grown at 130 K was only about a fifth to that grown at RT), it was drastically improved to reach the in-plane mean crystallite size of up to about 250 nm as the growth temperature was raised to 343 K. It is noteworthy that the crystallite size even shrunk when the growth temperature was above 363 K. This is presumably ascribed to re-sublimation of the substrate rubrene molecules and/or intermixing of rubrene and C 60 . For the case of tetracene, it was reported that surface roughening occurred by mild heating in vacuum [52]. On the other hand, in the previous literature [33], disordered structures are frequently recognized especially at step edges in the AFM images of the C 60 /RubSC formed at high temperatures, suggesting that formation of amorphous intermixture between C 60 and rubrene competed with assembly into the crystalized domains.…”
Section: Resultsmentioning
confidence: 95%